Empowering Pesantren Education: Overcoming Digitalization Challenges with Tsirwah Indonesia - Muhamad Syaikhu; Masduki, Masduki (Educational Insights, 2025)
This study examines the role of Tsirwah Indonesia in addressing the challenges of digitalization in pesantren, focusing on programs such as Mondok Online, digital skills training, and the development of applications for distance learning. Tsirwah Indonesia plays a crucial role in improving digital literacy among santri and expanding access to pesantren education in the digital era. These programs also support government policies aimed at creating a digitally literate society, particularly in the education sector through the Indonesia Digital 2045 initiative. This research adopts a qualitative approach using library research methods to analyze the implementation of digitalization in pesantren and its impact on educational quality. The findings reveal that digitalization not only enhances access to education but also supports the wider spread of Islamic teachings, reaching a global audience. Furthermore, this study discusses the challenges in implementing digitalization policies and provides recommendations for further development. The digitalization of pesantren education, as implemented by Tsirwah Indonesia, offers significant opportunities to address the educational challenges in the modern era.